2021
DOI: 10.55713/jmmm.v31i1.1008
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of solid acids in the Rb3H(SO4)2-RbHSO4 system under ambient atmosphere

Abstract: The thermal behavior of solid acids in the Rb3H(SO4)2-RbHSO4 system under ambient atmosphere has been studied in comparison to the previously reported high-temperature behavior of the same system under humidified atmosphere. The findings showed that, under this level of humidity, the transition of RbHSO4, the transition of Rb5H3(SO4)4, and the disproportionation of Rb3H(SO4)2, occurred at the same temperatures as those under humidified atmosphere. However, the results from differential scanning calorimetry did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The findings indicate that the nanosensors under investigation exhibit exceptional sensitivity, selectivity, and superior detection capabilities across all the metal ions considered. Furthermore, our study revealed that these nanosensors exhibit notably low detection limits and superior efficiency in comparison to previously reported findings by other researchers 33–40 . Table 4 provides a comparative analysis of distinct characteristics of the present sensing system with other optical sensors and spot test methods.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The findings indicate that the nanosensors under investigation exhibit exceptional sensitivity, selectivity, and superior detection capabilities across all the metal ions considered. Furthermore, our study revealed that these nanosensors exhibit notably low detection limits and superior efficiency in comparison to previously reported findings by other researchers 33–40 . Table 4 provides a comparative analysis of distinct characteristics of the present sensing system with other optical sensors and spot test methods.…”
Section: Resultssupporting
confidence: 55%
“…Furthermore, our study revealed that these nanosensors exhibit notably low detection limits and superior efficiency in comparison to previously reported findings by other researchers. [33][34][35][36][37][38][39][40] Table 4 provides a comparative analysis of distinct characteristics of the present sensing system with other optical sensors and spot test methods. The results presented in the table shows that the sensitivity of the present optical sensor for the detection of the metal ions was very high compared to other methods.…”
Section: Mesoporous Materialsmentioning
confidence: 99%